Learning translation rules for a bidirectional English-Filipino machine translator - Tan, Michelle Wendy G. (Animo Repository, 2006)
Filipino is a changing language that poses several challenges. Our goal is to develop a bidirectional English-Filipino Machine Translation (MT) system using a hybrid approach to learn rules from examples. The first phase was an English to Filipino MT system that required several language resources. The problem lies on its dependency over the annotated grammar which is currently unavailable for Filipino, which makes reverse translation impossible. Phase 2 addresses this limitation by using information taken from English and Filipino POS Taggers. The seed rules are generated by aligning the POS tags from English and Filipino examples, including their constraints. To perform compositionality, the system deduces the constituent labels by using the longest adjacent POS tags found in both the English and Filipino rule. The system groups together similar rules and generalizes it to encompass a wider range of unseen examples.